2019
DOI: 10.1002/ecs2.2590
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on shrub cover and shrub–shrub competition in a U.S. southwest desert

Abstract: The cover of woody perennial plants (trees and shrubs) in arid ecosystems is at least partially constrained by water availability. However, the extent to which maximum canopy cover is limited by rainfall and the degree to which soil water holding capacity and topography impacts maximum shrub cover are not well understood. Similar to other deserts in the U.S. southwest, plant communities at the Jornada Basin Long‐Term Ecological Research site in the northern Chihuahuan Desert have experienced a long‐term state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 69 publications
0
28
1
Order By: Relevance
“…When considering the rate of survival for Ephedra nevadensis within a year, the values are more similar, 7.4% (Ackerman, 1979). Low light conditions were observed to reduce the establishment rates and growth of Ephedra californica , but this is typical of desert shrub species that avoid growing under other shrub canopies (Martínez‐Tillería et al , 2012; Wu and Yang, 2013; Ji et al , 2019). Native shrubs, such as Ephedra californica , are well adapted to desert conditions suggesting propagation in the field could be successful for restoration of the San Joaquin Desert.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the rate of survival for Ephedra nevadensis within a year, the values are more similar, 7.4% (Ackerman, 1979). Low light conditions were observed to reduce the establishment rates and growth of Ephedra californica , but this is typical of desert shrub species that avoid growing under other shrub canopies (Martínez‐Tillería et al , 2012; Wu and Yang, 2013; Ji et al , 2019). Native shrubs, such as Ephedra californica , are well adapted to desert conditions suggesting propagation in the field could be successful for restoration of the San Joaquin Desert.…”
Section: Discussionmentioning
confidence: 99%
“…Lagomorph densities can influence herbivory pressure on rangelands (Norris 1950, Johnson and Anderson 1984, Mcadoo et al 1987, Havstad et al 1999), and shrub encroachment can intensify herbivory rates and potentially reinforce grassland loss (Bestelmeyer et al 2007, Kerley and Whitford 2009, Abercrombie et al 2019). If shrub cover is a good predictor of perceived risk, then mapping shrub cover via remote sensing (Ji et al 2019) could predict where seedling establishment for grasses will be constrained on the landscape, which could then inform state transition dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Shrub encroachment is exceedingly evident in the northern Chihuahuan Desert of the southwestern United States (Van Auken 2000, Peters et al 2012, Bestelmeyer et al 2018, Ji et al 2019). Over the last 150 yr, perennial grasslands have been invaded by native honey mesquite ( Prosopis glandulosa ) and creosote bush ( Larrea tridentata ) producing dramatic ecological state transitions (Buffington and Herbel 1965, Grover and Musick 1990, Peters et al 2006, 2012, Bestelmeyer et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been assumed that deserts are unproductive and exhibit low competition because of their scarcity of water (Grime, 1973; Huston, 1979; Gaudet and Keddy, 1989). However, studies have revealed a diverse spatial distribution of desert plants, and have shown how competition among plants can vary in levels of intensity (Fonteyn and Mahall, 1978; Fowler, 1986; Kadmon, 1995; Ji et al, 2019). In particular, plant removal experiments in arid regions have suggested that interspecific competition is more intense than intraspecific competition (Fonteyn and Mahall, 1978) while experiments along productivity gradients revealed a positive relation between competition and plant density (Kadmon, 1995).…”
Section: Introductionmentioning
confidence: 99%